Preparation process and application of environment-friendly waterborne polyurethane grouting material doped with nano graphene and biological oxidized hydroxyapatite

By introducing additives and other additives such as nanohide and biological oxidized hydroxide hydroxylite to form a composite self -catalytic repair system, the existing water -based polyurethane has the problem of poor sealing effects in the large flow surge scenarios, achieving high efficient plugging blocked blocked blockers Water and self -cultivation function.

CN119331206APending Publication Date: 2025-01-21XINYU RECORD TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411693778.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-25
Publication Date
2025-01-21

AI Technical Summary

Technical Problem

When faced with large flow water influx and environmentally closed scenarios, the existing water-based polyurethane grouting materials have poor sealing effect, the solidified body is easy to float, and some raw materials are highly toxic or easy to hydrolyze, resulting in poor application effect.

Method used

Adding additives such as nano -graphene and biological oxide hydroxide, combined with isocyanate groups to form a composite self -catalytic repair system to enhance the elasticity, hardness, and anti -aging capabilities of polyurethane. ability.

Benefits of technology

Realize the water -based polyurethane with high emulsification, strong watery, rapid solidification, strong re -absorbing and expanding ability, strong elasticity and strong adhesion. It has a self -repair function, which can effectively block the gaps of large flowing water and provide long -term stable water blocking performance.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to an environment-friendly water-soluble single-component polyurethane grouting material and a preparation process thereof. According to the environment-friendly water-soluble single-component polyurethane grouting material, nano graphene and biologically oxidized hydroxyapatite subjected to crystal stabilization are introduced into a formula to be combined with phenyl polyisocyanate and polyether polyol; and adding a catalyst, a chain extension cross-linking agent, a plasticizer and a diluent according to a specific proportion, and compounding. Wherein the nano graphene is ground to 5-50nm by a special ball mill, and the biological oxidized hydroxyapatite is sintered at a high temperature of 400-800 DEG C and is subjected to crystal arrangement in a hydrothermal kettle at a temperature of 90-120 DEG C; the environment-friendly water-soluble single-component polyurethane doped with the nano graphene and the biologically oxidized hydroxyapatite subjected to crystal regulation can meet the long-term plugging requirement of a large number of water gushing gaps, and can play a reinforcing role in movable gaps, and the self-repairing performance of the polyurethane can face multiple times of tearing of the gaps; meanwhile, the waterborne polyurethane also has the characteristics of low TVOC (Total Volatile Organic Compounds), environment friendliness and no odor.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of waterborne polyurethane, and more specifically to a preparation process and an application method of a self-repairing waterborne polyurethane which can be injected into a mine cave or a tunnel where a large amount of water seepage occurs to seal cracks, remove water, and reinforce structures. Background Art

[0002] Grouting is a common construction technology used to repair cracks in buildings, dams, reservoirs, etc. caused by improper construction and unstable foundations, and to plug leaks, waterproof, prevent seepage, and reinforce coal mines, subways, geological drilling, and other fields.

[0003] Grouting can improve the impermeability and integrity of the grouting base or building, improve the foundation conditions, and ensure the safe operation of the building. Common grouting materials include solid grouting and chemical grouting. Solid grouting is easy to obtain, low in cost, and simple to construct, but the width of the gap it can fill is limited by the fineness of its solid particles and has poor elasticity.

[0004] Chemical grouting uses a low-viscosity liquid with good fluidity made from chemical agents to plug leaks. It has good groutability and permeability, and the curing time can be selected. Common chemical grouting materials include water glass, acrylic gel, methyl gel, polyurethane, modified epoxy resin, lignin, etc.

[0005] Most chemical slurries have low reactivity at low temperatures and are limited to grouting stable cracks, poor elasticity and toughness of consolidated materials, and greater environmental pollution.

[0006] Polyurethane grouting materials are highly active, can be constructed with water, have good elasticity and strength, and are non-toxic. They are widely used grouting materials. Currently, there are two types: single-liquid type and double-liquid type.

[0007] Most two-liquid types are foamed polyurethane, which produces a large amount of carbon dioxide when it comes into contact with water, and then expands and solidifies, eventually forming a water-insoluble solid body. However, its water blocking effect is poor in scenes with large water output and fast flow rate. The solid body produced floats on the water and cannot stop the water in time. In addition, some raw materials are highly toxic or easily hydrolyzed and produce substances that accelerate the hydrolysis of the solid body. These characteristics lead to its extremely poor application effect in scenes with large flow of water and closed environment.

[0008] Single-liquid polyurethane is often water-soluble and can form an emulsion with water. The emulsion solidifies later and wraps water into the polyurethane to form a paste or block-like substance. However, its water-encapsulation is unstable, it is easy to seep water after encapsulation, and its water absorption capacity is poor after dehydration. It cannot play a reinforcing role in structural gaps, and other materials are needed for reinforcement later. It also has poor anti-corrosion ability and cannot self-repair.

[0009] Tunnels and mines often have large water inflows, fragile structural gaps that need to be reinforced, multiple leak repairs that are not conducive to construction periods, and high requirements for material durability. Therefore, it is urgent to develop water-based polyurethanes that have large water-packing capacity, rapid curing, low water seepage, strong reabsorption capacity, durability, certain elastomeric properties, can reinforce structural gaps, and have certain self-repairing capabilities. Utility Model Content

[0010] The technical problem to be solved by the present invention is to overcome the defects of water-based polyurethane grouting materials in the prior art and provide a synthesis process and application method of a water-soluble one-component polyurethane, thereby preparing a one-component water-soluble polyurethane with fast emulsification, strong water-encapsulating property, rapid curing, strong re-absorption and swelling ability, strong elasticity and adhesion, and self-repairing function.

[0011] The present invention specifically introduces nanographene and bio-oxidized hydroxyapatite into the single-component waterborne polyurethane, which can enhance the elasticity, hardness and anti-aging ability of the polyurethane after being wrapped in water. After the polyurethane is torn, the composite self-catalytic repair system formed by the two and the isocyanate groups in the polyurethane can repair the cracks, thereby extending the plugging time.

[0012] The present invention innovatively performs secondary processing on bio-oxidized hydroxyapatite to change its crystal form and make it more capable of binding with isocyanate. First, the cow bone powder or coral bone powder is roasted at 400-800°C to promote the formation of hydroxyapatite crystals. Second, the obtained hydroxyapatite crystals are shaped using a hydrothermal kettle at 90-120°C to make their crystal structure more uniform, the active sites more exposed, and the binding activity with isocyanate stronger.

[0013] The reaction temperature and the ratio of graphene and bio-oxidized hydroxyapatite to isocyanate groups controlled by the present invention can greatly enhance the repair ability, system ductility and hardness in the composite self-catalytic repair system.

[0014] The single-component water-soluble polyurethane obtained by the present invention can be used to seal gaps with large water inflow such as mine caves and tunnels, and the low-viscosity slurry can be pressed into deeper and finer cracks through the pressure during solidification and expansion, playing a certain supporting and bonding role in the deformation of the cracks, thereby playing a reinforcing role in the cracks in tunnels and mine caves, and having a certain self-repairing ability in the face of material cracks caused by unstable bottom layers.

[0015] The invention provides a method for preparing a water-soluble single-component polyurethane, which comprises: degassing and dehydrating a polyol (A) which is liquid at room temperature, has a molecular weight of 2000-8000 and a hydroxyl value of 15.5-56 mgKOH / g at 110-130°C and a vacuum degree of 1-3 mmHg.

[0016] The cow bone powder or coral bone powder is roasted at 400-800°C to promote the formation of hydroxyapatite crystals, and the obtained hydroxyapatite crystals are shaped by a hydrothermal reactor at 90-120°C to obtain bio-oxidized hydroxyapatite (B).

[0017] The graphene sheet is ground by a ball mill to obtain nanographene (C) with a particle size of 5nm-50nm.

[0018] Mix polyol (A), polyisocyanate (D), ammonia catalyst (E), tin catalyst (F), chain extender crosslinker (G), nanographene (C), bio-oxidized hydroxyapatite (B), etc., and react at 50-120°C for 3-6 hours. After the reaction, add plasticizer (H) and diluent (I) at 30-70°C and continue stirring for 0.5-3 hours.

[0019] Preferably, in the present invention, the polyol (A) is a homopolymer or copolymer of propylene oxide and a polyol, etc., including but not limited to homopolymers or copolymers formed by the reaction of propylene oxide, ethylene oxide, etc. with glycerol, propylene glycol, ethanolamine, diethanolamine, trimethylolpropane, pentaerythritol, ethylenediamine, diethylenetriamine, xylitol sorbitol, mannitol, etc. Polyisocyanates (D) such as methylene polyphenyl polyisocyanate PAPI and diphenylmethane diisocyanate MDI are obtained by condensing aniline and formaldehyde solution (formalin) under the action of Lewis acid to form a polyamine mixture containing a certain amount of diamines, and then such polyamine compounds are obtained by phosgenation reaction.

[0020] Preferably, the ammonia catalyst (E) can be triethylenediamine solution, brand A-33; bis(dimethylaminoethyl) ether solution, brand A-1; bis(dimethylaminoethyl) glycol ether solution, brand Jeffcat E-40; dimethylcyclohexylamine solution, brand Polycat 8; N-ethylmorpholine, brand Jeffcat NEM, etc.

[0021] Preferably, the tin catalyst (F) can be stannous octoate solution, brand T-9, dibutyltin dilaurate solution, brand T-12, di(dodecylsulfide) dibutyltin solution, brand T-120, etc.

[0022] Preferably, the chain extending crosslinking agent (G) may be 1,4-butanediol, ethylene glycol, glycerol, 1,6-hexanediol, trimethylolpropane, or the like.

[0023] Preferably, the nanographene (C) is a product of graphene powder or graphene flakes after grinding.

[0024] Preferably, the bio-oxidized hydroxyapatite (B) is a product obtained by processing bovine bone meal or coral bone meal.

[0025] Preferably, the plasticizer (H) may be dioctyl phthalate DOP, dibutyl phthalate DBP, diisodecyl phthalate DIDP, or the like.

[0026] Preferably, the diluent (I) may be ethyl acetate, dicarboxylic acid esters, acetone, isoamyl acetate, ethylene glycol diacetate, or the like.

[0027] Preferably, in addition to the above components, the water-soluble one-component polyurethane of the present invention may optionally contain additives for polyurethane, such as stabilizers, fillers, dyes, foaming aids, mold release agents, and the like.

[0028] The stabilizer can be an antioxidant, such as sterically hindered phenol, a UV absorber, such as UV-1, UV-1229, SAS, etc., a hydrolysis stabilizer, such as carbodiimide and polycarbodiimide, or a bactericidal and mildew-proof agent, such as isothiazolinone, pyrithione, etc.

[0029] The foaming agent may be a foaming agent such as dichloromethane, dimethyl ether, etc., and may be a foam stabilizer such as silicone, L580, NiaxL3627, etc.

[0030] The pore opening agent may be liquid paraffin, polybutadiene, dimethyl polysiloxane, etc.

[0031] The demoulding agent may be polydimethylsiloxane, paraffin oil, polyethylene wax, etc.

[0032] The fillers may be calcium carbonate, kaolin, pyroxene powder, talc, mica powder, titanium dioxide, silica powder, carbon black, glass fiber, gypsum powder, calcium sulfate, barite powder, barium sulfate, etc.

[0033] The emergency waterborne polyurethane for mine tunnels according to the present invention has excellent reactivity, water-encapsulating property and rehydration property after dehydration, and the gel produced after reaction with water has excellent elasticity, support, strength and hydrolysis resistance stability. It is used for rapid water blocking of large flow water gaps in tunnels or mines. The gel formed after a period of grouting reaction has high strength and has a certain reinforcement effect on the gaps, and the long-term use performance of the gel will not be significantly reduced. Therefore, this waterborne polyurethane is suitable for water blocking and reinforcement of mines, tunnels and other fissures with a large amount of water gushing out. DETAILED DESCRIPTION

[0034] Example 1

[0035] The present embodiment provides a synthesis process of waterborne polyurethane, comprising the following raw materials in parts by weight: 165 parts of polyisocyanate, 450 parts of polyol, 10 parts of chain extender crosslinker, 3 parts of amine catalyst, 2 parts of tin catalyst, 20 parts of nanographene, 30 parts of bio-oxidized hydroxyapatite, 145 parts of plasticizer, 145 parts of diluent, 20 parts of hydrolysis stabilizer, 5 parts of pore opener, and 5 parts of bactericidal and mildew-proof agent.

[0036] The polyisocyanate is PAPI, the polyol is polyether polyol with a molecular weight of 4000, the amine catalyst is A33, the tin catalyst is T9, the chain extender cross-linker is glycerol, the graphene is flaky graphene powder, the bio-oxidized hydroxyapatite is bovine bone powder, the plasticizer is dioctyl phthalate DOP, the diluent is acetone, the hydrolysis stabilizer is polycarbodiimide, the pore opener is dimethyl polysiloxane, and the bactericidal and mildew-proof agent is isothiazolinone.

[0037] S1: Weigh the raw materials in proportion, add the polyether polyol into the reactor, start the stirrer, dehydrate at 120°C and 1 mmHg vacuum for 1 hour, and then cool to about 60°C.

[0038] S2: Put the flake graphene into a ball mill and grind it to a particle size of 10nm-30nm.

[0039] S3: Put the bio-oxidized hydroxyapatite into a muffle furnace and calcine at 650℃ for 3h, take the calcined sample and put it into a hydrothermal reactor, add alanine and glutamic acid, hydrothermally react at 100℃ for 10h, and then vacuum dry at 120℃ for 1h.

[0040] S4: Add PAPI, catalysts A33 and T9, nanographene particles, and treated bio-oxidized hydroxyapatite into the reactor, slowly raise the temperature to 70-90°C, and react for 3 hours.

[0041] S5: Add cross-linking chain extender glycerol into the reactor, react at 75°C for 1 hour, and then cool down to about 40°C.

[0042] S6: Add dioctyl phthalate DOP and polycarbodiimide into the reactor and stir for 20 minutes.

[0043] S7: Continue to add acetone, dimethylpolysiloxane and isothiazolinone, continue stirring for 1 hour, and then terminate the reaction.

[0044] The polyurethane synthesized in this embodiment is suitable for use in cracks with damaged structures and large amounts of water gushing out. When used in tunnels and mines, it can provide long-term and stable water blocking performance. The gel formed is relatively hard and large, has strong elasticity and good support, and can reinforce the damaged parts of the structure and inhibit the contraction and expansion of the cracks. Moreover, the tearing of the polyurethane caused by the displacement of the crack can be repaired due to its self-repairing function.

[0045] Example 2

[0046] The present embodiment provides a synthesis process of waterborne polyurethane, comprising the following raw materials in parts by weight: 170 parts of polyisocyanate, 465 parts of polyol, 20 parts of chain extender cross-linking agent, 5 parts of tin catalyst, 20 parts of nanographene, 30 parts of bio-oxidized hydroxyapatite, 155 parts of plasticizer, 100 parts of diluent, 25 parts of hydrolysis stabilizer, 5 parts of pore opener, and 5 parts of bactericidal and mildew-proof agent.

[0047] The polyisocyanate is PAPI, the polyol is polyether polyol with a molecular weight of 6000, the tin catalyst is T9, the chain extender and cross-linker is glycerol, the graphene is flaky graphene powder, the bio-oxidized hydroxyapatite is bovine bone powder, the plasticizer is dioctyl phthalate DOP, the diluent is acetone, the hydrolysis stabilizer is polycarbodiimide, the pore opener is dimethyl polysiloxane, and the bactericidal and mildew-proof agent is isothiazolinone.

[0048] S1: Weigh the raw materials in proportion, add the polyether polyol into the reactor, start the stirrer, dehydrate at 120°C and 1 mmHg vacuum for 1 hour, and then cool to about 60°C.

[0049] S2: Put the flake graphene into a ball mill and grind it to a particle size of 10nm-30nm.

[0050] S3: Put the bio-oxidized hydroxyapatite into a muffle furnace and calcine at 650℃ for 3h, take the calcined sample and put it into a hydrothermal reactor, add alanine and glutamic acid, hydrothermally react at 100℃ for 10h, and then vacuum dry at 120℃ for 1h.

[0051] S4: Add PAPI, catalyst T9, graphene particles, and treated bio-oxidized hydroxyapatite into the reactor, slowly raise the temperature to 70-90°C, and react for 3 hours.

[0052] S5: Add cross-linking chain extender glycerol into the reactor, react at 75°C for 1.5 hours, and then cool to about 40°C.

[0053] S6: Add dioctyl phthalate DOP and polycarbodiimide into the reactor and stir for 20 minutes.

[0054] S7: Continue to add acetone, dimethylpolysiloxane and isothiazolinone, continue stirring for 1 hour, and then terminate the reaction.

[0055] The polyurethane synthesized in this embodiment is suitable for use in cracks with damaged structures and large amounts of water gushing out. When used in tunnels and mines, it can provide long-term and stable water blocking performance. The gel formed has moderate hardness, good toughness, and certain support. It can reinforce the expansion joints of damaged structures and inhibit the contraction and expansion of the cracks. The tearing of the polyurethane caused by crack displacement can be repaired due to its self-repairing function.

[0056] Example 3

[0057] The present embodiment provides a synthesis process of waterborne polyurethane, comprising the following raw materials in parts by weight: 140 parts of polyisocyanate, 90 parts of polyol A, 360 parts of polyol B, 10 parts of chain extender cross-linking agent, 5 parts of tin catalyst, 20 parts of nanographene, 30 parts of bio-oxidized hydroxyapatite, 190 parts of plasticizer, 120 parts of diluent, 25 parts of hydrolysis stabilizer, 5 parts of pore opener, and 5 parts of bactericidal and mildewproofing agent.

[0058] The polyisocyanate is PAPI, polyol A is a polyether polyol with a molecular weight of 2000, polyol B is a polyether polyol with a molecular weight of 8000, the tin catalyst is T12, the chain extender and cross-linker is glycerol, the graphene is flaky graphene powder, the bio-oxidized hydroxyapatite is bovine bone powder, the plasticizer is dioctyl phthalate DOP, the diluent is acetone, the hydrolysis stabilizer is polycarbodiimide, the pore opener is dimethyl polysiloxane, and the bactericidal and mildew-proof agent is isothiazolinone.

[0059] S1: Weigh the raw materials in proportion, add polyether polyol A and B into the reactor, start the stirrer, dehydrate at 120°C and 1 mmHg vacuum for 1 hour, and then cool to about 60°C.

[0060] S2: Put the flake graphene into a ball mill and grind it to a particle size of 10nm-30nm.

[0061] S3: Put the bio-oxidized hydroxyapatite into a muffle furnace and calcine at 650℃ for 3h, take the calcined sample and put it into a hydrothermal reactor, add alanine and glutamic acid, hydrothermally react at 100℃ for 10h, and then vacuum dry at 120℃ for 1h.

[0062] S4: Add PAPI, catalyst T12, graphene particles, and treated bio-oxidized hydroxyapatite into the reactor, slowly raise the temperature to 70-90°C, and react for 4 hours.

[0063] S5: Add cross-linking chain extender glycerol into the reactor, react at 75°C for 1 hour, and then cool down to about 40°C.

[0064] S6: Add dioctyl phthalate DOP and polycarbodiimide into the reactor and stir for 20 minutes.

[0065] S7: Continue to add acetone, dimethylpolysiloxane and isothiazolinone, continue stirring for 1 hour, and then terminate the reaction.

[0066] The polyurethane synthesized in this embodiment is suitable for use in cracks with damaged structures and large amounts of water gushing out. When used in tunnels and mines, it can provide long-term and stable water blocking performance. The gel formed is relatively soft, has strong toughness, strong adhesion and rehydration, has certain support, can be used to reinforce movable expansion joints, and has a much stronger ability to repair polyurethane tears caused by crack displacement than in Examples 1 and 2.

Claims

1. An environmentally friendly waterborne polyurethane grouting material doped with nanographene and bio-oxidized hydroxyapatite, characterized in that: It is mainly prepared from the following raw materials in parts by weight: 400-500 parts of polyether polyol, 120-200 parts of polyisocyanate, 5 parts of catalyst, 10-20 parts of chain extender and crosslinker, 20 parts of nanographene, 30 parts of bio-oxidized hydroxyapatite, 100-200 parts of plasticizer, 100-200 parts of diluent, 15-30 parts of stabilizer, and 0-5 parts of pore opener; The polyether polyol is selected from homopolymers or copolymers of propylene oxide, ethylene oxide, etc. and polyols; the polyisocyanate is methylene polyphenyl polyisocyanate PAPI and diphenylmethane diisocyanate MDI; the catalyst is mainly composed of ammonia catalysts A33, A1, etc. and tin catalysts T9, T12, etc.; the chain extender crosslinker is mainly composed of polyols such as glycerol and trimethylolpropane; the nanographene is a graphene particle with a size of 5-50 nm after grinding of block graphene; the biooxidized hydroxyapatite is a bovine bone powder or coral bone powder baked at 400-800°C. The product is sintered and crystallized and then subjected to hydrothermal autoclave crystallization at 90-120°C; the plasticizer is selected from one of dioctyl phthalate DOP, dibutyl phthalate DBP and diisodecyl phthalate DIDP; the diluent is selected from one of ethyl acetate, dicarboxylic acid ester, acetone and isoamyl acetate; the stabilizer can be an antioxidant such as UV-1, UV-1229, SAS, etc., a hydrolysis stabilizer such as carbodiimide, polycarbodiimide, etc., a bactericidal and mildewproof agent such as isothiazolinone, pyridinethione, etc.; the pore opening agent can be liquid paraffin, polybutadiene, dimethylpolysiloxane, etc.

2. The environmentally friendly waterborne polyurethane grouting material doped with nanographene and bio-oxidized hydroxyapatite according to claim 1, characterized in that: It is mainly composed of the following raw materials in parts by weight: 140-200 parts of polyisocyanate, 300-500 parts of polyether polyol, 5 parts of catalyst, 10-20 parts of chain extender cross-linking agent, 20 parts of nanographene, 30 parts of bio-oxidized hydroxyapatite, 100-200 parts of plasticizer, 100-200 parts of diluent, 15-30 parts of stabilizer, and 0-5 parts of pore opener.

3. The environmentally friendly waterborne polyurethane grouting material doped with nanographene and bio-oxidized hydroxyapatite according to claim 2, characterized in that: It is mainly prepared from the following raw materials in parts by weight: 170 parts of polyisocyanate, 465 parts of polyether polyol, 5 parts of catalyst, 20 parts of chain extender cross-linking agent, 20 parts of nanographene, 30 parts of bio-oxidized hydroxyapatite, 155 parts of plasticizer, 100 parts of diluent, 25 parts of hydrolysis stabilizer, 5 parts of pore opener, and 5 parts of bactericidal and mildew-proof agent.

4. The environmentally friendly waterborne polyurethane grouting material doped with nanographene and bio-oxidized hydroxyapatite according to any one of claims 1 to 3, characterized in that: Its ingredients also include foaming agents such as dichloromethane, dimethyl ether, etc., and foam stabilizers such as L580, NiaxL3627, etc.

5. The environmentally friendly waterborne polyurethane grouting material doped with nanographene and bio-oxidized hydroxyapatite according to any one of claims 1 to 4, characterized in that: Its ingredients also include fillers such as calcium carbonate, kaolin, pyroxene powder, talc, mica powder, titanium dioxide, silica powder, carbon black, glass fiber, gypsum powder and calcium sulfate, barite powder and barium sulfate.

6. The environmentally friendly waterborne polyurethane grouting material doped with nanographene and bio-oxidized hydroxyapatite according to any one of claims 1 to 5, characterized in that: It uses specially ground nanographene with a particle size of 5-50nm.

7. The environmentally friendly waterborne polyurethane grouting material doped with nanographene and bio-oxidized hydroxyapatite according to any one of claims 1 to 6, characterized in that: The method uses bovine bone powder or coral bone powder which is calcined at 400-800°C for crystallization and then hydrothermally processed at 90-120°C to obtain biologically oxidized hydroxyapatite crystals.

8. The process for preparing the environmentally friendly waterborne polyurethane grouting material doped with nanographene and bio-oxidized hydroxyapatite according to any one of claims 1 to 7, characterized in that: The following steps are also included: According to the composition of the environmentally friendly waterborne polyurethane grouting material doped with nanographene and bio-oxidized hydroxyapatite as claimed in any one of claims 1 to 7, the raw materials are weighed, the polyol is degassed and dehydrated at 110-130° C. and a vacuum degree of 1-3 mmHg, polyisocyanate, catalyst, chain extender, crosslinking agent, nanographene, and bio-oxidized hydroxyapatite are added, and the reaction is carried out at 50-120° C. for 3-6 hours. After the reaction is completed, a plasticizer and a diluent are added at 30-70° C. and stirring is continued for 0.5-3 hours.